Analisis Pengelolaan Keuangan Terhadap Efektifitas Penggunaan Dana Bantuan Operasional Sekolah (BOS ) Pada Sma Negeri 1 Lasusua Kabupaten Kolaka Utara Provinsi Sulawesi Tenggara - Ramli; Pasulu, Milka; Rina (STIM-LPI Makassar, 2025)
That this study aims to determine the management of BOS funds at SMA Negeri 1 Lasusua, Lasusua District, with planning aspects, namely the timely preparation of the RKAS, namely at the beginning of the budget year, the use of a priority scale for school needs and the involvement of teachers and school committees in the BOS budget preparation meeting (RKAS)The results of the study indicate that the implementation of BOS management at SMA Negeri 1 Lasusua has been successful based on the technical instructions for the use of BOS Funds in 2023, but there are often delays in the distribution of BOS funds which make the use of BOS Funds slightly hampered but immediately implemented when BOS Funds are distributed, BOS fund reporting at SMA Negeri 1 Lasusua has met the criteria, namely the school makes a report for each stage and makes a report on the realization of the use of BOS funds at the end of each semester and is submitted to the Provincial BOS Team for review.